(untitled) (World Science, 2020)
Prior to a surgery for diaphragmatic dome relaxation a patient sought consultation of an orthopedic traumatologist about his concomitant spinal diseases. The patient’s symptoms could describe both diaphragmatic relaxation and multiple spinal pathologies complicated by rib displacement. Thorough diagnostics and careful analysis followed by subsequent manual correction of the patient’s skeletal misalignments allowed to relieve all pain, restore the patient’s ability to work and prevent an unreasonable and traumatic surgery which was in fact unnecessary and unjustifiably harmful as it wouldn’t solve the problem of pain caused by the pathologies in the costovertebral area and could potentially lead to the patient’s disability. As for diaphragmatic relaxation, it was asymptomatic in the first place and never actually required surgery. It is therefore important to exercise a great degree of responsibility when diagnosing complex clinical cases.